2020
DOI: 10.1177/0267659120952057
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of trimetazidine on contrast-induced nephropathy undergoing percutaneous coronary intervention in elderly moderate and high risk diabetics stratified by mehran score

Abstract: Background: The aim of this research was to use the Mehran risk score to classify elderly diabetics with coronary heart disease to assess the preventive effect of trimetazidine on contrast-induced nephropathy (CIN) after percutaneous coronary intervention (PCI) in different risk population. Methods: An uncompromised of 760 elderly diabetics that went through PCI were included in this research. The patients were first divided into three groups in the light of MRS: low-risk, moderate-risk, and high-risk group, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Five trials [18,19,21,22,25] reported the eGFR 72 hours after contrast medium exposure. The eGFR was higher in the probucol with hydration group than the hydration-only group (MD: 5.94, 95% CI: 3.70–8.17, P < .001; I 2 = 2%, P = .39, fixed effect model; Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five trials [18,19,21,22,25] reported the eGFR 72 hours after contrast medium exposure. The eGFR was higher in the probucol with hydration group than the hydration-only group (MD: 5.94, 95% CI: 3.70–8.17, P < .001; I 2 = 2%, P = .39, fixed effect model; Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The same results were observed for the Scr level after 48 hours (MD: -13.78, 95% CI: -22.08 to -5.49, P = .001; I 2 = 91%, P < .001; random effect model, 6 trials [12,13,16,17,21,24] ; Table 2 and Fig. 6B) and 72 hours (MD: -8.76, 95% CI: -12.25 to -5.26, P < .001; I 2 = 82%, P < .001, random effect model, 12 trials [12,13,[16][17][18][19][20][21][22][23][24][25] ; Table 2 and Fig. 6C).…”
Section: Other Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has the potential to be used to treat the metabolic remodeling of heart failure (HF). TMZ can inhibit the excessive release of oxygen-free radicals, increase glucose metabolism, limit intracellular acidosis, and prevent the accumulation of protons, sodium, and calcium in muscle cells during cardiac ischemic [9, 39, 40]. Besides beneficial effects on the heart, several studies have shown the protective effects of TMZ on kidney injury [8-12, 14, 15, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies showed that 3-KAT in the mitochondrial matrix inhibit pyruvate dehydrogenase. Thus, by inhibiting 3-KAT, TMZ could increase pyruvate dehydrogenase activity, which in turns substantially increase myocardial glucose oxidation and increase the oxygen use during myocardial hypoxia [40, 43]. In addition, Li et al [43] proposed that a potential mechanism for the cardioprotective effect of TMZ linked with the regulation of adenosine monophosphate-activated protein kinase expression, where activation of adenosine monophosphate-activated protein kinase in turns increase glucose uptake via glucose transporter 4, and increase fatty acid uptake and oxidation by increasing the activity of carnitine palmitoyltransferase 1.…”
Section: Discussionmentioning
confidence: 99%